Tail-flick-est - aspects use in pharmacological researches - T. V. Kava; O. E. Yadlovskiy (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The adequate assessment of anti-nociceptive activity is important. This is necessary for development of new analgesics that exceed effectiveness and/or safety of existing analgesics, fundamental research, study specifics pharmacodynamics of known analgesics. Рurpose of work is scientific and methodical analyze approaches to study of antinociceptive activity with Tail-flick test. The study was carried out using databases on the Internet using science-based databases: PubMed, Medline, Europe PMC, FDA, EMA, Google Scholar. Methods of approach to planning, conducting an experiment, interpretation of the received data were analyzed. It were use retrospective, logical and system-analytical research methods. It has analyzed the level scientific physiological, pharmacological, and experimental data of anesthetic activity evaluation of Tail-flick-test. The method has several advantages, among them: simplicity, lack special skills from experimenter, effectiveness for screening opioid and other analgesics, the accuracy of the results of the experiment and moderate time consumption of experiment. But method has some disadvantages, namely: adaptation animals to nociceptive irritation (re-stimulation, especially when reducing the intervals between measurements; increase intensity radiation). Tail-flick-test did not reveal appropriate efficacy study anti-nociceptive activity of opioid receptor antagonist- agonists. Thus, the Tail-flick test is one of the most adequate methods for Tail-flick-test is informative to study of the opioid component of analgesics. The accuracy and adequacy of the experimental data depends on the characteristics of the experiment setting and the rules for conducting the research.